Beta Adrenergic Receptors Stimulation Attenuates Phosphorylation of NF-κB and IκBα in Hyperglycemic Endothelial Cells - Safi, Sher Zaman; Shah, Humaira; Qvist, Rajes; Bindal, Priyadarshni; Mansor, Marzida; Ong, Gracie Siok Yan; Ismail, Ikram Shah (Karger Publishers Open Access, 2018)
Background/Aims: NF-κB induces transcription of a number of genes, associated with inflammation and apoptosis. In this study, we have investigated the effect of β-adrenergic receptor stimulation on NF-κB and IκBα in HUVECs. Methods: Human umbilical vein endothelial cells (HUVECs) were cultured in high and low glucose concentrations. All HUVECs were treated with different concentrations of isoproterenol and propranolol for different time periods. The analytical procedures consisted of Western Blot, ELISA, DCFH-DA and TUNEL assays. Results: Isoproterenol (agonist of a beta-adrenergic receptor) significantly reduced phosphorylation at Ser-536 of NF-κB; and Ser-32 and Ser-36 of IκBα in hyperglycemic HUVECs. Isoproterenol also significantly reduced apoptosis and ROS generation. No effect of IκBα was observed on Tyr-42 phosphorylation. The effect of isoproterenol was reversed by the antagonist propranolol. We also checked if NF-κB inhibitor MG132 causes any change at the level of apoptosis. However, we observed an almost similar effect. Conclusion: Given data demonstrates that beta-adrenergic receptors stimulation has a protective effect on HUVECs that might be occuring via NF-κβ and IκBα pathway.